Memantine: procognitive and antinegative effects in mental illness (a literature review) - D. V. Romanov; P. G. Yuzbashyan (Неврология, нейропсихиатрия, психосоматика)
According to the instruction approved in the Russian Federation, Akatinol Memantine is indicated for the treatment of all types of dementia regardless of its severity. In addition, data are being accumulated on the use of memantine in a wide range of mental disorders, including schizophrenia, bipolar affective disorder, recurrent depression, obsessive-compulsive disorder, etc.This review is devoted to the analysis of an update on adjuvant therapy with memantine for the above mental disorders. It discusses the precogni-tive and antinegative effects of the drug in schizophrenia on the basis of the data of meta-analyses and double-blind, placebo-controlled studies.